2017
DOI: 10.14252/foodsafetyfscj.2016028
|View full text |Cite
|
Sign up to set email alerts
|

Atypical BSE: Current Knowledge and Knowledge Gaps

Abstract: Atypical BSE is an invariably fatal neurologic disease of cattle caused by misfolded prion proteins with different conformations than those associated with classical BSE. Evidence suggests that these atypical BSE types are sporadic or genetic prion diseases of cattle and the relevance of these diseases, as far as natural transmissibility, is still unknown. Different misfolded prion protein conformations also result in unique biochemical characteristics. This raised concerns about detection of atypical BSE on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…However, since the three Holstein cattle carrying the K211 somatic mutation in the medulla oblongata were not investigated as to whether K211 somatic mutation could be observed in other brain regions, it is difficult to conclude that this somatic mutation was only found in the medulla oblongata. In addition, since atypical BSE has shown to be a prominent brain pathology in the frontal cortex [ 17 , 18 ], if the atypical BSE was caused by a somatic mutation of the PRNP gene, it is expected that the somatic mutation was also found in the cerebral cortex. Thus, further investigation of the K211 somatic mutation is highly desirable in other brain regions, including the cerebral cortex of the three Holstein cattle carrying K211 somatic mutation in the medulla oblongata.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the three Holstein cattle carrying the K211 somatic mutation in the medulla oblongata were not investigated as to whether K211 somatic mutation could be observed in other brain regions, it is difficult to conclude that this somatic mutation was only found in the medulla oblongata. In addition, since atypical BSE has shown to be a prominent brain pathology in the frontal cortex [ 17 , 18 ], if the atypical BSE was caused by a somatic mutation of the PRNP gene, it is expected that the somatic mutation was also found in the cerebral cortex. Thus, further investigation of the K211 somatic mutation is highly desirable in other brain regions, including the cerebral cortex of the three Holstein cattle carrying K211 somatic mutation in the medulla oblongata.…”
Section: Discussionmentioning
confidence: 99%
“…However, novel forms of BSE and atypical BSEs have been reported in many countries. Unlike classical BSE, the cause of atypical BSE has not been determined [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this finding, atypical BSE cases have been reported in countries such as Norway, Romania, and Brazil, where no C-BSE cases were reported 80) . Therefore, the occurrence of H-BSE and L-BSE was unlikely due to feed-mediated infection, but is likely due to sporadic nature 17,81) L-BSE can be readily transmitted to various animals by experimental infection. The experiments using bovine-PrP overexpressing Tg (Tgbov XV) mice, human-PrP overexpressing Tg mice, macaques, and cattle have suggested that the virulence of L-BSE (BASE) is higher than that of C-BSE 18,[82][83][84] .…”
Section: Transmission Characteristics Of Atypical Bsementioning
confidence: 99%
“…They also differ from Norwegian reindeer CWD and from CWD strains in North America [ 12 , 13 ]. They are thought to represent sporadic prion disease as has been described in other species, rather than contagious CWD [ 14 16 ]. In 2020, a new case of contagious CWD was discovered in a wild reindeer on the Hardanger mountain plateau south of Nordfjella [ 17 ], representing a new geographical region for infection.…”
Section: Introductionmentioning
confidence: 99%